2021
DOI: 10.1111/lang.12443
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Mechanisms Underlying Second Language Achievement: A Regulatory Focus Perspective

Abstract: We tested a theoretical model that integrated regulatory focus, second language (L2) self-guides, anxiety and enjoyment, eager and vigilant L2 use, and L2 achievement. We collected data from 324 students learning English as a foreign language. Structural equation modeling results showed that (a) the promotion focus positively predicted ideal selves, whereas the prevention focus negatively predicted ought selves; (b) ideal self/own predicted enjoyment positively and anxiety negatively, ought self/other and idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
86
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(103 citation statements)
references
References 64 publications
13
86
4
Order By: Relevance
“…The results of the present study suggest that the promotion regulatory focus could contribute to the level of pragmatics competence. Creating a promotionfocused learning environment and adopting a promotionfocused approach that encourages risk-taking, engagements, creativity, and eagerness in teaching L2 pragmatics could thus have positive effects on L2 learners' learning behavior and outcomes (see Papi and Khajavy, 2021). Promotionfocused instructional and classroom management styles such as minimizing error correction and maximizing learners' opportunities to talk in the classroom could elicit language learners' engagement and eagerness, and benefit L2 pragmatics learning.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the present study suggest that the promotion regulatory focus could contribute to the level of pragmatics competence. Creating a promotionfocused learning environment and adopting a promotionfocused approach that encourages risk-taking, engagements, creativity, and eagerness in teaching L2 pragmatics could thus have positive effects on L2 learners' learning behavior and outcomes (see Papi and Khajavy, 2021). Promotionfocused instructional and classroom management styles such as minimizing error correction and maximizing learners' opportunities to talk in the classroom could elicit language learners' engagement and eagerness, and benefit L2 pragmatics learning.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang and Papi (2021) found that a promotion focus negatively predicts L2 speaking anxiety among Chinese learners of English. In Iran, Papi and Khajavy (2021) found that a promotion focus positively predicted ideal L2 selves, which in turn contributed to the emotion of L2 enjoyment, an eager L2 use inclination, and L2 achievement. On the other hand, a prevention focus negatively predicted ought L2 selves, which in turn positively predicted L2 anxiety and vigilant L2 use.…”
Section: Regulatory Focus Theorymentioning
confidence: 99%
See 3 more Smart Citations